2016
DOI: 10.1111/jopr.12533
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Cytotoxicity of Maxillofacial Silicone Elastomers: Effect of Nano‐particles

Abstract: Nanoparticles of TiO , fumed silica, and silaned silica added to a commercial silicone-based elastomer used for fabrication of maxillofacial prostheses are nontoxic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…showed that nanoparticles such as nano-TiO 2 , fumed silica, and silaned silica added to a silicone-based elastomer used for fabrication of maxillofacial prostheses are nontoxic. [ 29 ] Other nanoparticles like ZnO, CeO 2 , BaSO 4 , Al 2 O 3 , SiO 2 , POSS which were used to improve the properties of silicone elastomer material requires evaluation of their biocompatibility in future research [ Table 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…showed that nanoparticles such as nano-TiO 2 , fumed silica, and silaned silica added to a silicone-based elastomer used for fabrication of maxillofacial prostheses are nontoxic. [ 29 ] Other nanoparticles like ZnO, CeO 2 , BaSO 4 , Al 2 O 3 , SiO 2 , POSS which were used to improve the properties of silicone elastomer material requires evaluation of their biocompatibility in future research [ Table 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Assessment of cell viability was performed based on a previous study [25]. Cytotoxicity was assessed with a tetrazolium salt 3-[4,5-dimethylthiazol-2-yl]-2,5-diphnyltetrazolium bromide (MTT) (M5655; Sigma-Aldrich, St. Louis, MO, USA) assay.…”
Section: Cell Viability Assessmentmentioning
confidence: 99%
“…Nanoparticles of TiO 2 , smoldered silica, and silaned silica added to a silicone-based elastomer utilized for the manufacture of maxillofacial prostheses were found to be nontoxic. 47 Monodispersed polystyrene particles, with distances in the scope of many nanometers, were infused onto the stretched film. Furthermore, a close-pressed monolayer of particles was self-collected and connected on the best surface of the film because of its viscidity.…”
Section: Efficient Electrical Energy With Dielectric Elastomersmentioning
confidence: 99%